Fracture of inferior vena cava stent after endovascular treatment for Budd-Chiari syndrome: A case series and literature review - Pengxu Ding; Wen Zhou; Jiayin Ding; Shaofeng Shui; Luo Xu; Edward Wolfgang Lee (Journal of Interventional Medicine, 2023)
Budd-Chiari syndrome (BCS) is a rare condition characterized by hepatic venous outflow obstruction. Balloon angioplasty, with or without stenting, is the recommended first-line treatment modality in Asian countries. As a supplement to balloon angioplasty, expandable metallic Z-stent deployment can effectively improve long-term inferior vena cava (IVC) patency. Although stent placement is a standard and frequently performed treatment, very few IVC stent-related complications, such as stent fractures, have been reported. Here we present a case series and a comprehensive review of IVC stent fractures in patients with BCS. The most common characteristic of IVC stent fractures is a protrusion of the proximal segment of the IVC stent into the right atrium and its systolic and diastolic movements along with heart rhythms. Accurate stent deployment, large-diameter balloon dilation, patient breath-holding training, preferential selection of a triple stent, and the use of an internal jugular vein approach to stent deployment may ensure precise stent localization and avoid postoperative complications.